Enhancing motivation for initiation and continuation of physical activity in older adults using sensory augmentation devices: a preliminary pre–post study - Yusuke Sakaue; Yurie Kondo; Masaaki Makikawa; Naruhiro Shiozawa; Motoyuki Iemitsu; Tetsuo Yoshimoto; Shima Okada (Frontiers in Sports and Active Living)
Improvement of physical and cognitive capabilities through physical activity (PA) contributes to well-being in older age. Unfortunately, many older adults lack sufficient PA, due to reasons such as PA not being enjoyable for them. As a result, older adults are unable to maintain their motivation for the initiation and continuation of PA. In our previous works, a boxing glove-type sensory augmentation system was developed to solve this problem by inducing enjoyment during PA. However, the effect of our device on physical and cognitive capabilities, which are crucial for well-being, and motivation for initiation and continuation of PA remains unclarified. In this study, we aimed to evaluate these effects. We hypothesized that our device may help improve capabilities, and that the enjoyment it provides may potentially contribute to increased motivation for initiation and continuation of PA. Fourteen healthy older adults participated in the study. Kickboxing lessons for the older adults using our device were conducted a total of five times over a six-week period, and the participants were free to attend the sessions as many times as they wished. They participated in three measurement sessions: pre-measurement before the lesson period, post-lesson measurement after each lesson, and post-measurement at the end of the lesson period to evaluate the effects of our device. Physical capabilities were assessed through two-step, stand-up, and center-of-pressure tests. Cognitive capabilities were assessed using illustration memory and computation tests. Mental state was assessed using a positive and negative affect schedule (PANAS). Subjective evaluations of enjoyment and motivation for the initiation and continuation of PA through the use of our device were also conducted. In the results, physical and cognitive capabilities and mental states tended to improve. Subjective evaluations indicated increased enjoyment from using our device and greater perceived effectiveness in motivating PA initiation and continuation. These evaluations improved over time. While the pre-post design without a control group limits causal interpretation, improvements in physical, cognitive, and mental states may have contributed to enhanced enjoyment. As a result, the device may have the potential to enhance motivation for initiation and continuation PA in older adults.